Triangular test design to evaluate tinidazole in the prevention of Plasmodium vivax relapse. - Macareo, L; Lwin, K; Cheah, P; Yuentrakul, P; Miller, R; Nosten, F (2013)
BACKGROUND: There are very few drugs that prevent the relapse of Plasmodium vivax malaria in man. Tinidazole is a 5-nitroimidazole approved in the USA for the treatment of indications including amoebiasis and giardiasis. In the non-human primate relapsing Plasmodium cynomolgi/macaque malaria model, tinidazole cured one of six macaques studied with an apparent mild delay to relapse in the other five of 14-28 days compared to 11-12 days in controls. One study has demonstrated activity against P. vivax in man. Presented here are the results of a pilot phase II, randomized, open-label study conducted along the Thai-Myanmar border designed to evaluate the efficacy of tinidazole to prevent relapse of P. vivax when administered with chloroquine. METHODS: This study utilized a modified triangular test sequential analysis which allows repeated statistical evaluation during the course of enrolment while maintaining a specified power and type 1 error and minimizing recruitment of subjects. Enrolment was to be halted when a pre-specified success/failure ratio was surpassed. The study was designed to have a 5% type 1 error and 90% power to show whether tinidazole would produce a relapse rate of less than 20% or greater than 45% through Day 63 of weekly follow-up after initiation of treatment and initial parasite clearance with 3 days of an oral weight based dosing of chloroquine and five days of 2 grams/day of tinidazole. RESULTS: All subjects cleared their parasitaemia by Day 3. Six of the first seven subjects treated with tinidazole relapsed prior to Day 63 (average Day 48.3 (range 42-56)). This exceeded the upper boundary of the triangular test and enrolment to receive tinidazole was halted. A concurrent cohort of five subjects definitively treated with standard doses of primaquine and chloroquine (historically 100% effective) showed no episodes of recurrent P. vivax parasitaemia during the 63-day protocol specified follow-up period. CONCLUSIONS: Tinidazole is ineffective in preventing relapse of P. vivax at the dose used. The macaque relapsing model appeared to correctly predict outcome in humans. Use of the modified triangular test allowed minimal enrolment and limited unnecessary exposure to the study drug and reduced costs. This adds weight to the ethical and economic advantages of this study design to evaluate similarly situated drugs. TRIAL REGISTRATION: ClinicalTrials.gov NCT00811096.